Automating inequality : how high-tech tools profile, police, and punish the poor - Eubanks, Virginia, 1972- (New York : Picador ; St. Martin's Press, 2019)
"Since the dawn of the digital age, decision-making in finance, employment, politics, health and human services has undergone revolutionary change. Today, automated systems control which neighborhoods get policed, which families attain resources, and who is investigated for fraud. While we all live under this new regime of data, the most invasive and punitive systems are aimed at the poor. Virginia Eubanks systematically investigates the impacts of data mining, policy algorithms, and predictive risk models on economic inequality and democracy in America."--Front jacket flap.
Introduction: Red flags -- From poorhouse to database -- Automating eligibility in the heartland -- High-tech homelessness in the City of Angels -- The Allegheny algorithm -- The digital poorhouse -- Conclusion: dismantling the digital poorhouse -- Acknowledgments -- Sources and methods -- Notes -- Index.
Includes bibliographical references and index.
Keywords: Poor -- Services for -- United States -- Data processing; Poverty -- United States